Protrusion and Actin Assembly are Coupled to the Organization of Lamellar Contractile Structures - Lim, James I. (2010)
Directed cell migration requires continuous cycles of protrusion of the leading edge and contraction to pull up the cell rear. How these spatially distributed processes are coordinated to maintain a state of persistent protrusion remains unknown. During wound healing responses of epithelial sheets, cells along the wound-edge display two distinct morphologies: ‘Leader cells’ exhibit persistent edge protrusions, while the greater majority of ‘follower cells’ randomly cycle between protrusion and retraction. Here, we exploit the heterogeneity in cell morphodynamic behaviors to deduce the requirements in terms of cytoskeleton dynamics for persistent and sporadic protrusion events. We used quantitative Fluorescent Speckle Microscopy (qFSM) to compare rates of F-actin assembly and flow relative to the local protrusion and retraction dynamics of the leading edge. Persistently protruding cells are characterized by contractile actomyosin structures that align with the direction of migration, with converging F-actin flows interpenetrating over a wide band in the lamella. Conversely, non-persistent protruders have their actomyosin structures aligned perpendicular to the axis of migration, and are characterized by prominent F-actin retrograde flows that end into transverse arcs. Analysis of F-actin kinetics in the lamellipodia showed that leader cells have threefold higher assembly rates when compared to followers. To further investigate a putative relationship between actomyosin contraction and F-actin assembly, myosin II was inhibited by blebbistatin. Treated cells at the wound edge adopted a homogeneously persistent protrusion behavior, with rates matching those of leader cells. Surprisingly, we found that disintegration of actomyosin structures led to a significant decrease in F-actin assembly. Our data suggests that persistent protrusion in these cells is achieved by a reduction in overall F-actin retrograde flow, with lower assembly rates now sufficient to propel forward the leading edge. Based on our data we propose that differences in the protrusion persistence of leaders and followers originate in the distinct actomyosin contraction modules that differentially regulate leading edge protrusion-promoting F-actin assembly, and retraction-promoting retrograde flow.